2001
DOI: 10.1002/ajim.1060
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and other respiratory symptoms in New Zealand pine processing sawmill workers

Abstract: Working in pine sawmilling is associated with an increased prevalence of asthma and cough symptoms and eye and nose irritation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 23 publications
3
43
1
1
Order By: Relevance
“…Other studies also found that complaints concerning eyes and nose were most frequent [9,11,19,20,22,30]. We also have found that, the complaints of redness of the eyes, rhinorrhea, nasal blockade, runny nose and sore throat were more frequent among the workers working for 10 years or more compared with those working for less than 10 years.…”
Section: O R I G I N a L P A P E R S Ijomeh 2009;22(1) 47supporting
confidence: 55%
See 1 more Smart Citation
“…Other studies also found that complaints concerning eyes and nose were most frequent [9,11,19,20,22,30]. We also have found that, the complaints of redness of the eyes, rhinorrhea, nasal blockade, runny nose and sore throat were more frequent among the workers working for 10 years or more compared with those working for less than 10 years.…”
Section: O R I G I N a L P A P E R S Ijomeh 2009;22(1) 47supporting
confidence: 55%
“…International Agency for Research on Cancer (IARC) reports that wood dust causes cancer and included it in 1995 into Group 1 carcinogens [1]. Besides, wood contains many microorganisms (including fungi), toxins and chemical substances and they may significantly affect human health [1,2,[8][9][10]. It is recognised that those agents may cause irritation of oral cavity and throat, tightness of the chest, irritant dermatitis, urticaria, alveolitis, deterioration of pulmonary functions, and a reduction of FEV 1 [1,2,7,[10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This possibility could mean either that even a rather low exposure to wood dust can increase the risk of developing persistent asthma or it could be that, in the group of other bluecollar workers, also other (nonwood dusts) industrial exposures play an important role. There is increasing evidence that asthma and other respiratory symptoms occur already at low wood dust levels (11,16,21). The relation between occupational exposures and asthma is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of all cases of occupational asthma due to wood dust has been reported to be some 6-11% (8). Asthma induced by western red cedar has been frequently documented for sawmill workers, with an apparent dose-response relationship (10)(11)(12)(13)(14). The studies proposing a relationship between exposure to other softwood species and asthma have used self-reported asthma (11) and clinically diagnosed asthma (15,16) as outcomes.…”
mentioning
confidence: 99%
“…Wood dust is recognized as a human carcinogen (2,3). Beside the carcinogenic effect, a number of epidemiological studies have identified wood dust as a risk factor for asthma or asthma symptoms (4)(5)(6), nasal impairment (7,8), and acute or chronic impairment of lung function (8-10) -all diseases consistent with both an allergic and a nonallergic origin.…”
mentioning
confidence: 99%